Uji Efektivitas Antihiperglikemia Ekstrak Daun Puring (Codiaeum variegatum) Terhadap Mencit Jantan (Mus musculus L.) - Faroliu, Goldha; Cici Adelia (Yayasan Rahmatan Fiddunya Wal Akhirah, 2024)
Diabetes mellitus (DM) is a metabolic disease due to insulin secretion disorders due to pancreatic cell damage. Puring plants (Codiaeum variegatum) in Indonesia are more identical as cemetery plants and garden decorations. The purpose of this study was to see the antihyperglycemic effect of croton leaf extract. This study was conducted by making croton leaf extract, phytochemical screening, and antihyperglycemia testing by observing the decrease in blood glucose levels in mice induced by alloxan. Based on the results of phytochemical tests, croton leaves contain compounds such as flavonoids, terpenoids, phenolics, saponins, and alkaloids. The flavonoid content found in plants has a role as an antihyperglycemic compound and antioxidant. The results of the study were analyzed by One Way ANOVA for the percentage parameter of blood glucose reduction and continued with the Tukey post hoc test. The results of observations showed that the administration of croton leaf extract in reducing blood glucose levels at a dose of 300 mg/kgBW, and showed no significant difference with the positive control group. The conclusion of this study is that a dose of 300 mg/kgBW of croton leaf extract is the best dose in reducing blood glucose levels in mice.